Evaluation of Taxpayer Compliance in Paying Land And Building Tax in Tomohon City (Study in Walian Satu Sub-District, South Tomohon District) - Lensun, Deiby; Pangkey, Itje; Tarore, Steven V. (Technium Social Sciences Journal, 2024)
This research aimed to analyze and evaluate of Taxpayer Compliance in Paying Land and Building Tax (PBB) in Walian Satu Sub-District, South Tomohon District, Tomohon City. This research approach uses a descriptive qualitative approach, with 10 predetermined informants using data collection techniques, namely observation, interviews, and documentation with data analysis techniques through data reduction, data presentation, and drawing verification conclusions. The results of this research show that in the Evaluation of Taxpayer Compliance in Paying Land and Building Tax (PBB) in Walian Satu Sub-District, South Tomohon District, Tomohon City, seen from the evaluation research sub-focus on Community Participation, Leadership, and Communication, there are several problem findings, namely 1) Lack of participation or activeness of the community in the process of paying taxes, 2) there is no intention or movement from the sub-district government to be able to carry out a special strategy to move the community in paying taxes 3) there is a sub-district government that has not provided an example of good leadership, lack of utilizing technology from the government to provide understanding to the public in paying taxes and 4) then there are findings that the government has not been effective in communicating between the government to the government and the government to the public. The advice that can be given is that the government should improve coordination with the community to build communication so that the community will better understand how important it is to pay Land and Building Tax.